Diasporic Chinese Community in Post-Conflict Aceh: Socio-Cultural Identities, and Social Relations with Acehnese Muslim Majority - Eka Srimulyani; Marzi Afriko; M. Arskal Salim; Moch. Nur Ichwan (Al-Jami'ah Research Centre, 2018)
This study examines the notions of identity among the minority groups of Chinese in Banda Aceh, Indonesia. It focuses on what has changed, what has been challenged and what is [still] continued, locating the discussion within a context of their social dialectics with the local majority of Muslims due to its time, spatiality and social processes. Admittedly, the history of diasporic Chinese and their social interrelation with the ethnic majority of Acehnese does not occur in static, but in a dynamic way, instead. It was continuously constructed, reconstructed and changed in a specific durability and spatiality within a negotiated space of socio-spatial dialectics between the minority and the local majority groups. Through several observations, and in-depth interviews with people from diasporic Chinese community in Banda Aceh, and with few Acehnese informants, this study discovers that some socio-political situations at macro-national level of the related policies (on minorities), as well as at micro-regional (provincial and municipal) ones, shari’a law application affected the way they interacted, responded, and acted with majority groups, with apparently more efforts being focused on creating non-conflict, harmonious relation with the local majority. Moreover, the efforts to becoming ‘part’ or accepted by the dominant culture is quite prevalent throughout the process, which is also combined with the strategy of building relation (social capital) with the local majority and other important stakeholders of the society, such as through their ethnic-based organization like Hakka, and others.[Tulisan ini menekankan pada pembahasan identitas orang Tionghoa di Banda Aceh pasca konflik Aceh. Fokus kajian meliputi perubahan, tantangan dan apa yang sedang terjadi dalam konteks dialektika sosial terhadap mayoritas penduduk muslim Aceh dalam waktu, ruang dan proses sosialnya. Tidak dapat dipungkiri bahwa sejarah hubungan Tionghoa dengan penduduk Aceh mengalami pasang surut. Hubungan tersebut terbentuk dan berubah dalam lingkup ruang dan durasi tertentu seiring dengan bentuk dialektikal komunitas Tionghoa sebagai minoritas dan penduduk muslim Aceh sebagai mayoritas. Berdasarkan pengamatan lapangan dan wawancara mendalam sejumlah informan dari kedua pihak, kajian ini melihat adanya pengaruh kebijakan level nasional terhadap situasi di tingkat provinsi dan kabupaten. Penerapan Hukum Islam juga mempengaruhi mereka berinteraksi, merespon dan bertindak terhadap kelompok mayoritas muslim dalam usaha membangun hubungan yang harmoni dan damai. Selain itu usaha untuk ‘menjadi bagian’ atau diterima oleh budaya dominan cukup menonjol dalam proses sosialnya yang dikombinasikan dengan strategi membangun modal sosial, baik terhadap penduduk muslim atau pejabat pemerintah, seperti misalnya organisasi Hakka.]